Autoimmune risk loci of IL12RB2, IKZF1, XKR6, TMEM39A and CSK in Chinese patients with systemic lupus erythematosus. Issue 3 (March 2015) - You, Y.; Zhai, Z. F.; Chen, F. R.; Chen, W.; Hao, F.
Abstract Recent genome‐wide or follow‐up studies conducted in European or Caucasian populations have identified single nucleotide polymorphisms (SNPs) conferring increased risk to autoimmune diseases. It is unclear whether these observations can apply to systemic lupus erythematosus (SLE) in China. An association study was performed on 395 SLE patients and 378 healthy controls recruited from the Chinese population, in which the IL12RB2 rs3790567, IKZF1 rs2366293, XKR6 rs4240671, TMEM39A rs1132200 and CSK rs34933034 polymorphisms were examined by Matrix Assisted Laser Desorption Time of Flight Mass Spectrometry. The frequency of the A allele of IL12RB2 rs3790567 was lower in the cases compared with the controls (24.8% vs 30.2%, P = 0.018) and significant difference among the AA, AG and GG genotypes of rs3790567 was detected between the SLE patients and healthy controls (P = 0.020). We also found a statistically significant difference in the dominant model (GG+AG vs AA, P = 0.008). There was no correlation between the genotypes and specific sub‐phenotypes in the current cohort. Associations with IKZF1 rs2366293, XKR6 rs4240671, TMEM39A rs1132200 and CSK rs34933034 were also lacking (P > 0.05). The results supported the theory that IL12RB2 is associated with SLE in the Chinese population.